2015
DOI: 10.1103/physrevc.92.045201
|View full text |Cite
|
Sign up to set email alerts
|

Baryon mass splittings and strongCPviolation in SU(3) chiral perturbation theory

Abstract: We study SU (3) flavor-breaking corrections to the relation between the octet baryon masses and the nucleon-meson CP -violating interactions induced by the QCDθ term. We work within the framework of SU (3) chiral perturbation theory and work through next-to-next-to-leading order in the SU (3) chiral expansion, which is O(m 2 q ). At lowest order, the CP -odd couplings induced by the QCDθ term are determined by mass splittings of the baryon octet, the classic result of Crewther et al. We show that for each isos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 125 publications
7
86
0
Order By: Relevance
“…[12,18,23] and references therein). The QCD Lagrangian with a nonzero θ term takes the following form:…”
Section: A Quark Mass and Qcd θ Termmentioning
confidence: 99%
See 3 more Smart Citations
“…[12,18,23] and references therein). The QCD Lagrangian with a nonzero θ term takes the following form:…”
Section: A Quark Mass and Qcd θ Termmentioning
confidence: 99%
“…For instance, Ref. [18] studied the higher-order effects to the matching formulas induced by a QCD θ term in a three-flavor ChPT. They found that, when the matching relation ofḡ (0) π is expressed in terms of the nucleon mass splitting, then its form is preserved by the chiral loop correction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, chiral symmetry relatesḡ θ 0 to known CP-even LECs [21,22]. In particular, it is possible to write [23] 9) where (M N − M P ) strong is the quark-mass induced part of the proton-neutron mass splitting,m = (…”
mentioning
confidence: 99%